2021
DOI: 10.1186/s12984-021-00928-x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the energy cost of running using a lightweight, low-profile elastic exosuit

Abstract: Background Human beings can enhance their distance running performance with the help of assistive devices. Although several such devices are available, they are heavy and bulky, which limits their use in everyday activities. In this study, we developed a lightweight running assistive device with a low-profile design. The device applies a flexion moment to the hip according to the hip extension within a specific range of motion to assist running. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Jin et al [ 61 ] proposed a soft wearable robot that utilized winding belts for power transmission, and then conducted evaluation experiments of metabolic cost on occasions when elderly persons were implementing long-distance level and inclined walking [ 68 ]. Some researchers made full use of elastic elements and textile materials to build passive exosuits and explored their biomechanical effects during walking [ 63 ] or running [ 64 ]. The prototype based on Bowden cables could deliver the motor output along a fixed path to the anchor point of the anterior thigh, and lead to a metabolic reduction effect as well [ 65 , 67 ].…”
Section: Overview Of Exosuitmentioning
confidence: 99%
See 1 more Smart Citation
“…Jin et al [ 61 ] proposed a soft wearable robot that utilized winding belts for power transmission, and then conducted evaluation experiments of metabolic cost on occasions when elderly persons were implementing long-distance level and inclined walking [ 68 ]. Some researchers made full use of elastic elements and textile materials to build passive exosuits and explored their biomechanical effects during walking [ 63 ] or running [ 64 ]. The prototype based on Bowden cables could deliver the motor output along a fixed path to the anchor point of the anterior thigh, and lead to a metabolic reduction effect as well [ 65 , 67 ].…”
Section: Overview Of Exosuitmentioning
confidence: 99%
“…The specific value is obtained by indirect measurement with a portable gas analysis system. Much research has measured carbon dioxide and oxygen rate to calculate metabolic power through a modified Brockway equation [ 50 , 64 ]. A large number of experimental results have proved that exosuits show an ability to reduce metabolic cost to different degrees.…”
Section: Key Technologiesmentioning
confidence: 99%
“…While passive systems can lower energy cost by moderate amounts, powered exoskeleton devices have the potential to provide larger reductions in the metabolic cost of running by injecting energy into the human-exoskeleton system. Passive support, which leverages the compliance and resilience of materials to provide a metabolic benefit, have included the Nike Vaporfly marathon shoe (4% reduction) [ 10 ]; a passive elastic hip exosuit (5% reduction) [ 11 ]; a rubber band connected between the feet (6% reduction) [ 12 ]; a passive exo-tendon hip exoskeleton (7% reduction) [ 13 ]; and a passive torsional spring hip exoskeleton (8% reduction) [ 14 ]. Powered untethered exoskeletons, however, could be especially helpful to individuals like novice or ageing runners who need larger metabolic reductions to perceive or benefit from assistance.…”
Section: Introductionmentioning
confidence: 99%
“…Jinsoo Kim et al showed that a portable exosuit carried on the back that assists hip extension can reduce the metabolic rate of treadmill walking at 1.5 m per second by 9.3% and that of running at 2.5 m per second by 4.0%, compared with locomotion without the exosuit [13]. Jaeha Yang et al proposed a passive exosuit (without power) which was fabricated using textile materials and elastic bands to assist hip flexion that can reduce the user's metabolism by 4% at a running speed of 2.5 m/s [14].…”
Section: Introductionmentioning
confidence: 99%